The Use of Electrical Cardiometry for Continuous Cardiac Output Monitoring in Preterm Neonates: A Validation Study - Song, R.; Rich, W.; Kim, J. H.; Finer, N. N.; Katheria, A. C. (American Journal of Perinatology, 2014)
Background Electrical cardiometry (EC) is a continuous noninvasive method for measuring cardiac output (CO), but there are limited data on premature infants. We evaluated the utility of EC monitoring by comparing the results obtained using EC to measurements of CO and systemic blood flow using echocardiography (ECHO).Methods In this prospective observational study, 40 preterm neonates underwent 108-paired EC and ECHO measurements.Results There were correlations between EC-CO and left ventricular output (LVO, p < 0.005) and right ventricular output (RVO, p < 0.005) but not with superior vena cava (r = 0.093, p = 0.177). Both RVO and LVO correlated with EC with and without a hemodynamically significant ductus arteriosus (p = 0.001 and 0.008, respectively). The level of agreement was decreased in infants ventilated by high-frequency oscillation ventilators (HFOV). The bias in HFOV was also positive compared with the negative biases found in other modes of ventilation.Conclusion Given the correlation of EC with LVO, RVO, and lack of confounding effects of the ductus, our results suggest that EC has promise for trending CO in the preterm infant. However, given the limitations with mode of ventilation and the lack of correlation at low LVO values, further study is needed before this technology can be for routine use.
Keywords: neonatology; cardiology; echocardiography; electrical cardiometry